The Effect of CEO Narcissism and Board Gender Diversity on Financial Performance of Indonesian Basic Materials Companies - Melliya Futri Octavianti Suhara; Dwi Jayanti (LifeSciFi, 2026)
Corporate financial performance is a crucial indicator of organizational sustainability and is influenced by various internal factors, including executive characteristics and corporate governance mechanisms. However, empirical findings regarding the influence of CEO narcissism and board gender diversity on corporate financial performance remain inconsistent. This study aims to examine the effect of CEO narcissism and board gender diversity on corporate financial performance, both partially and simultaneously, in basic materials companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employed a quantitative approach with an associative research design using secondary data obtained from audited annual reports. The sample was selected through purposive sampling, resulting in 16 companies with 64 observations. Data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis using IBM SPSS Statistics 26. The results indicate that CEO narcissism has a negative but insignificant effect on corporate financial performance, while board gender diversity also has a negative and insignificant effect. Simultaneously, CEO narcissism and board gender diversity do not significantly affect corporate financial performance. These findings suggest that executive characteristics and board composition alone are insufficient determinants of corporate financial performance, highlighting the importance of other strategic and operational factors.